Postharvest fruit quality of apple influenced by ethylene antagonist fumigation and ozonized cold storage. (30th March 2021) - Tokala, Vijay Yadav; Singh, Zora; Kyaw, Poe Nandar
Highlights: BC and NC fumigation retarded ethylene production and respiration in apple fruit. Ethylene antagonist fumigation reduced weight loss and loss of fruit firmness. Ozone increased ethylene production but maintained high levels of sugars in fruit. No interaction between ethylene antagonists and ozone in retarding ethylene production. Abstract: The effects of two new ethylene antagonists namely 1 H -cyclopropabenzene (BC) and 1 H -cyclopropa[ b ]naphthalene (NC), as well as 1-methylcyclopropene (1-MCP) on ethylene production and fruit quality of Cripps Pink and Granny Smith apple in ozonized cold storage, were investigated. When compared to control, Cripps Pink fruit fumigated with BC and NC exhibited significantly lowest ethylene production and respiration, whilst the Granny Smith fruit treated with 1-MCP exhibited lowest ethylene production followed by NC and BC treatments. Application of ozone in cold storage maintained higher levels of sugars but elevated ethylene production in both the apple cultivars. No significant interaction was recorded between ethylene antagonists and ozone application in cold storage on the ethylene production, respiration and other fruit quality parameters. In conclusion, results suggest that BC and NC are potential ethylene antagonists in Cripps Pink and Granny Smith apples during the cold storage.